From neuroinflammation to gliomagenesis: immune drivers of malignant transformation in the CNS - Bao, Yingshi; Chen, Zixuan; Su, Yutong; Guo, Tingting; Du, Huaping; Jia, Xianjun (Frontiers in Immunology, 2025)
Chronic neuroinflammation is increasingly recognized not merely as a consequence of CNS pathology but as a driver of glioma initiation. Sustained immune activation, induced by trauma, infection, or neurodegeneration, reshapes the brain’s immune milieu in ways that favor malignant transformation. Persistent inflammation activates glial cells, triggers cytokine release, and disrupts the blood-brain barrier, permitting immune infiltration and dysfunction. These changes promote the accumulation and reprogramming of immunosuppressive populations, including regulatory T cells and myeloid-derived suppressor cells, while resident microglia and astrocytes adopt tumor-supportive phenotypes. We highlight signaling axes such as IL-6/STAT3, NF-κB, and TGF-β that connect immune dysregulation to epigenetic instability and the emergence of glioma-initiating cells. By tracing the progression from inflammation to tumorigenesis, we identify opportunities for early immune-based intervention, particularly in individuals with chronic neuroinflammatory conditions.